Environmental pollution and economic growth in the European Union countries: A systematic literature review - Suproń, Błażej (Economics and Business Review, 2025)
This study presents a comprehensive analysis of the relationship between economic growth and CO₂ emissions in the European Union, with a particular focus on the Environmental Kuznets Curve (EKC) hypothesis. Through a systematic review of approximately 1,250 scientific publications, machine learning techniques, and multivariate statistical analysis, significant yet complex relationships between these variables have been identified. While the EKC hypothesis often posits a U-shaped or N-shaped relationship, the findings of this research indicate that the actual relationship can vary depending on factors such as foreign trade, energy consumption, and econometric methodologies. Numerous studies emphasise the importance of integrating renewable energy into these models. Overall, the results suggest that the EKC may be insufficient to fully comprehend the intricacies of sector-specific environmental-economic dynamics within the EU.